Many Sparrows [large type] : a novel - Benton, Lori (Center Point Large Print, 2018)
"When settler Clare Inglesby is widowed and her young son, Jacob, captured by Shawnees, she'll do anything to get him back. Frontiersman and adopted Shawnee, Jeremiah Ring, promises to help her recover Jacob. Once they reach the Shawnees and discover Jeremiah's own Shawnee sister has adopted Jacob, keeping his promise becomes far more complicated"--